Evaluation of the Programme of Mechanisation of Fishing Boats PEO Pub No. 72 - Planning Commission (Planning Commission, 1971)
The production of marine fish, mainly inshore in character, in terms of landings has increased at an average annual rate of 4.6 percent during the period 1961 to 1968. The export of marine products has also registered a significant increase over the years. From a level of Rs. 42 million in 1962-63, the export earning has jumped to Rs.. 247 million in 1968-69. This has been due not merely to the increase' in the quantities exported,
Programme Evaluation Organisation Planning Commission Government of India